Selection of the kinematic scheme and determination of the main characteristics of the generator-drive unit from the axis of the wheelset of a three-element freight bogie - V. G. Kargin; S. N. Naumenko; V. V. Burov; I. N. Chuvashov; S. L. Samoshkin (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
At present, large-capacity refrigerated containers (LCRC) are widely used for the transport of perishable goods. Transportation of such containers by rail is carried out by couplings of 10-12 fitting platforms and a car with diesel-electric power station. Analysis of this method of transporting large-capacity refrigerated containers by rail showed that it has a number of shortcomings that complicate the transportation process and increase the costs of the carrier (or perishable freight owner).Reduction of costs for the transportation of LCRC can be achieved by equipping the fitting platforms with an autonomous power supply system with a generator-drive unit (GPU) from the axis of the wheel pair of the bogie. However, most of the fitting platforms are installed on three-piece freight bogies, and this creates certain difficulties when embedding the GPU into the undercarriage space.Based on the performed analysis of domestic and foreign designs of generator-driven units and the results of studies for 18-100 three-element freight bogies, it is recommended to use a two-stage drive from the wheel pair axis consisting of a single-stage gear reducer and a V-belt drive, allowing to achieve a total gear ratio of 5,3.According to the chosen scheme, design documentation was developed and two prototypes were made. Experimental samples of GPU with a two-stage drive passed preliminary and acceptance tests, according to the results of which it is recommended to make an installation batch. At present, two 60-foot fitting platforms equipped with an autonomous power supply system are being manufactured for the purpose of carrying out running tests.